A thematic review of the patterns and research trends on household food waste management - Nik Masdek, Nik Rozana; Wong, Kelly Kai Seng; Sharifuddin, Juwaidah; Mohd Nawi, Nolita; Wong, Wang Li (Common Ground Research Networks, 2022)
Food waste is at the center of intense debate in the scientific arena. Food waste management has often been described as the key to food waste reduction, especially to reduce pressure on landfill sites. Households frequently contribute a large amount of food waste generation, making it a focal research point. Despite increasing publications on the continuous food waste issue, a review paper looking at the trends and patterns of household food waste management research is not readily available. Accordingly, this review is motivated by the belief that food waste management should be handled from the source, namely tackling household food waste. To achieve this purpose, this article will review current literature for the past five years on food waste management at the household level using thematic review via ATLAS.ti 8. A list of keywords related to the scope of review was identified. Following the identification of keywords, article search was conducted in Scopus and Web of Science. A total of seventy-five papers made it to the final stage, after going through the inclusion and exclusion process. A themed review was carried out, and five final themes were identified: technology and application; behavior and model development; policy and intervention; sustainability and circular economy; evaluation, assessment, and quantification. As a result, the pattern obtained from the thematic review highlighted existing gaps in the literature and suggests future research into food waste management at source, representing a significant contribution to research development in the future.